Implementasi Pendidikan Karakter Pada Pendidikan Non Formal Di Bimbingan Belajar Be Star Kelurahan Cempaga Kecamatan Bangli Kabupaten Bangli - A.A. Ayu Setiawati; I Nyoman Temon Astawa; Ni Wayan Satri Adnyani (Jurnal Penelitian Agama Hindu, 2019)
Character education is an effort to educate children so that they can make decision wisely and can practice them in their daily lives. Be Star tutoring is one of the non formal education that seeks to implement character education in the proses of tutoring and outside the prosess of tutoring. The problems to be discussed in this article are 1) Efforts in the implemention of character education in non formal education at Be Star tutoring in Cempaga Village Bangli District Bangli Regency. 2) Obstacles faced in the implementation of character education in non formal education at Be Star tutoring in Cempaga Village Bangli District Bangli Regency. 3) The role of teacher in implementation of charcter education at Be Star tutoring in Cempaga Village Bangli District Bangli Regency. The theories used to analyze the problems were Atitude Theory, Behavioristic Theory, Role Theory. Data collection methodes were observation, interviews, literature studies and documentation. The data that had been collected was analyzed through data reduction, data presentation, and conclusion drawing. The results of the study show 1) Efforts in the implemention of character education in non formal education in at Be Star tutoring in Cempaga Village Bangli District Bangli Regency that is habituation activities including routine activities and spontaneous activities of exemplary advice and the application of eighteen characters. 2). Obstacles faced in the implementation of character education in non formal education at Be Star tutoring in Cempaga Village Bangli District Bangli Regency namely the limited time and environment, the influence of information technology, as well as parenting. 3). The role of teacher in implementation of charcter education at Be Star tutoring in Cempaga Village Bangli District Bangli Regency namely as a teacher, as a role model, as an inspiration, as a motivator, as dynamisator, and evaluator.